Quality of life of children and their caregivers during an AOM episode: development and use of a telephone questionnaire - Dubé, Eve (BioMed Central, 2010)
BACKGROUND: The negative consequences of acute otitis media (AOM) on the quality of life (QOL) of children and their families need to be measured to assess benefits of preventive interventions. METHODS: A new questionnaire was specifically designed for use in telephone surveys. A random sample of Canadian families was selected using random-digit dialling. Caregivers of children 6-59 months of age who experienced at least one AOM episode during the last 12 months were interviewed. Multidimensional severity and global QOL scores were measured both for affected children and their caregivers. Internal consistency of scores was assessed using standard tests. RESULTS: Of the 502 eligible caregivers who completed the survey, 161 (32%) reported at least one AOM episode during the last 12 months and these cases were included in the analysis. Average severity was 2.6 for children and 2.4 for caregivers on a 1 to 4 scale (maximum severity). Cronbach alpha values were 0.78 and 0.81 for the severity score of children and caregivers respectively. Average QOL was 3.4 for children and 3.5 for caregivers on a 1 to 5 scale (best QOL). There was moderate to high correlation between severity and QOL scores, and between these scores and duration of AOM episodes. CONCLUSIONS: The questionnaire was easy to use during telephone interviews and results suggest good reliability and validity of the different scores to measure AOM severity and QOL of children and their caregivers during an AOM episode.